Underwater cultural heritage and international law - Dromgoole, Sarah (Cambridge : Cambridge University Press, 2013)
'The UNESCO Convention on the Protection of the Underwater Cultural Heritage 2001, which entered into force internationally in 2009, is designed to deal with threats to underwater cultural heritage arising as a result of advances in deep-water technology. However, the relationship between this new treaty and the UN Convention on the Law of the Sea is deeply controversial. This study of the international legal framework regulating human interference with underwater cultural heritage explores the development and present status of the framework and gives some consideration to how it may evolve in the future. The central themes are the issues that provided the UNESCO negotiators with their greatest challenges: the question of ownership rights in sunken vessels and cargoes; sovereign immunity and sunken warships; the application of salvage law; the ethics of commercial exploitation; and, most crucially, the question of jurisdictional competence to regulate activities beyond territorial sea limits.'--Publisher
1. The evolution of international law on underwater cultural heritage -- 2. Defining underwater cultural heritage -- 3. Ownership and other interests in underwater cultural heritage -- 4. Sunken warships and other state vessels and aircraft -- 5. Application of salvage law and the law of finds -- 6. Commercial exploitation of underwater cultural heritage -- 7. Rights, jurisdiction and duties under general international law -- 8. UNESCO Convention 2001: jurisdictional mechanisms -- 9. UNESCO Convention 2001: implementation issues -- 10. UNESCO Convention 2001: further matters.
Includes bibliographical references (pages 375-387) and index.
Keywords: UNESCO; Convention on the Protection of Underwater Cultural Heritage -- (2001); Underwater archaeology -- Law and legislation; Cultural property -- Protection (International law)